PENGGUNAAN METODE RESITASI DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SD NEGERI - Karudin Djonler; Muhamad Sidiq Asyhari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the low level of student participation and learning outcomes in Islamic Religious Education (PAI) at SD Negeri 2 Pucungkidul. The learning process was still predominantly teacher-centered, causing students to be less active, independent, and responsible in completing learning tasks. Therefore, an effective instructional method was needed to improve students' learning outcomes. This study aimed to describe: (1) the implementation of the recitation method in Islamic Religious Education learning, (2) the effectiveness of the recitation method in improving students' learning outcomes, and (3) the supporting and inhibiting factors influencing its implementation. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving the Islamic Religious Education teacher and students of SD Negeri 2 Pucungkidul. The data were analyzed using the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings showed that the recitation method was implemented systematically through lesson planning, task assignment, supervision, and evaluation. The method successfully improved students' activeness, discipline, responsibility, and understanding of learning materials, resulting in better learning outcomes. Supporting factors included teacher competence, student motivation, adequate learning facilities, parental support, and a conducive school environment. Meanwhile, the inhibiting factors were differences in students' academic abilities, limited instructional time, low learning motivation among some students, and inadequate parental supervision. Overall, the recitation method proved to be an effective learning strategy for improving learning outcomes in Islamic Religious Education at the elementary school level. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya keaktifan dan hasil belajar siswa pada mata pelajaran Pendidikan Agama Islam (PAI) di SD Negeri 2 Pucungkidul. Proses pembelajaran masih didominasi oleh guru sehingga siswa cenderung pasif, kurang mandiri, dan belum memiliki tanggung jawab yang optimal dalam menyelesaikan tugas pembelajaran. Kondisi tersebut menunjukkan perlunya penerapan metode pembelajaran yang mampu meningkatkan keterlibatan siswa serta hasil belajar secara lebih efektif. Penelitian ini bertujuan untuk mendeskripsikan: (1) pelaksanaan metode resitasi dalam pembelajaran Pendidikan Agama Islam, (2) keberhasilan metode resitasi dalam meningkatkan hasil belajar siswa, dan (3) faktor pendukung serta faktor penghambat dalam penerapan metode resitasi. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data diperoleh melalui observasi, wawancara, dan dokumentasi dengan melibatkan 1 guru Pendidikan Agama Islam, 1 kepala sekolah, dan 3 siswa SD Negeri 2 Pucungkidul sebagai informan penelitian. Analisis data dilakukan melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diuji menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa metode resitasi dilaksanakan melalui perencanaan pembelajaran, pemberian tugas, pembimbingan, dan evaluasi hasil tugas. Penerapan metode ini mampu meningkatkan keaktifan, kedisiplinan, tanggung jawab, serta pemahaman siswa terhadap materi pembelajaran sehingga berdampak pada peningkatan hasil belajar. Faktor pendukung meliputi kompetensi guru, motivasi belajar siswa, ketersediaan sarana pembelajaran, dukungan orang tua, dan lingkungan sekolah yang kondusif. Sementara itu, faktor penghambat meliputi perbedaan kemampuan akademik siswa, keterbatasan waktu pembelajaran, rendahnya motivasi sebagian siswa, dan kurangnya pendampingan orang tua di rumah.